A game model for information dissemination in live streaming e‐commerce environment. (18th October 2021) - Lv, Junjie; Yao, Wenjing; Wang, Yuanzhuo; Wang, Zichen; Yu, Jianye
Summary: As a new form of social e‐commerce, live streaming e‐commerce is becoming increasingly popular among Chinese consumers. Live streaming brings huge opportunities, and we can take measures to further expand the dissemination of live streaming information. A live streaming information dissemination game model based on social evolutionary game theory is presented to simulate multiple complex live streaming e‐commerce networks. The introduction of incentive mechanism in the model further quantifies the internal relation between rewards and live streaming information dissemination to a certain extent and predicts the ratings of live streaming in networks with different update frequency of social relationships. The simulation results indicate that the reputation environment in social networks, adjusting frequency of relationship, pre‐broadcast rewards to post‐broadcast rewards ratio all have certain ranges of impact on information dissemination in live streaming e‐commerce environment and then affect the live streaming ratings. These findings offer insights into the dissemination of live streaming information in social networks. Abstract : We investigate the internal mechanism of live streaming information dissemination by constructing a model. The simulation results indicate that rewards have direct effect on the information dissemination in low‐reputation environment, and the effect declines with the network reputation increases. Furthermore, increasing interaction in a high‐reputation environment can facilitate the dissemination of live streaming information.